Hyperacute Perfusion Imaging Before Pediatric Thrombectomy: One Step Closer. (14th March 2023) - Stence, Nicholas; Dlamini, Nomazulu
Abstract : The use of advanced neuroimaging techniques that identify the ischemic core and the penumbra (surrounding brain tissue that has the potential for recovery) has been critical to the success of multicenter randomized controlled trials of hyperacute therapies aimed at restoring perfusion and minimizing injury related to large vessel occlusion stroke in adults. However, in the acute setting of childhood stroke, the implementation of perfusion imaging has been hampered by developmental (age-related differences in cerebral blood flow), clinical (time to diagnosis, stroke etiology, and intracranial arteriopathy), and technical (contrast delivery in acute setting and availability of software) challenges.